Positive electrode material and secondary battery

By reinstalizing the lithium iron phosphate material of large grains and small grains to form new positive electrode materials, the problem of insufficient power performance of lithium ion batteries in low SOC and low temperature and low SOC state, realized the energy density of the battery Increase the capacity maintenance rate.

CN119381412APending Publication Date: 2025-01-28ENVISION DYNAMICS TECH (JIANGSU) CO LTD +4
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202310922328.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-26
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

The lithium-ion batteries of the existing lithium iron phosphate system are insufficient in low SOC and low temperature and low SOC states, making it difficult to meet the high requirements for battery performance of the entire vehicle.

Method used

By completion of the lithium iron phosphate material with a grain size greater than or equal to 80nm, the lithium iron phosphate material with a grain size of less than 80nm is compounded to form a new positive pole material. The positive pole material can continue to provide lithium embedded points in a low SOC state to improve the power performance of the battery.

Benefits of technology

It significantly improves the power performance of lithium -ion batteries in low SOC and low temperature and low SOC state, and enhances the energy density and capacity maintenance rate of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119381412A_ABST
    Figure CN119381412A_ABST
Patent Text Reader

Abstract

The invention provides a positive electrode material and a secondary battery, and particularly relates to the technical field of secondary batteries. The positive electrode material comprises a first active substance and a second active substance, the grain size d1 of the first active substance is larger than or equal to 80 nm, and the grain size d2 of the second active substance is smaller than 80 nm. The large-grain active substance can improve the energy density of the battery cell, and the power performance of the secondary battery in a low SOC state can be effectively improved by compounding a certain proportion of small-grain active substance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of secondary batteries, and in particular to a positive electrode material and a secondary battery. Background Art

[0002] Secondary batteries are the most commonly used battery technology and are widely used in consumer electronics, electric vehicles, and various portable electronic devices. In secondary batteries, the positive electrode material has an important influence on the performance of the battery. At present, the mainstream positive electrode materials of secondary batteries include: lithium iron phosphate (LiFePO4), lithium cobalt oxide (LiCoO2), lithium manganese oxide (LiMn2O4), nickel cobalt manganese ternary material (Ni-Co-Mn), nickel cobalt aluminum ternary material (Ni-Co-Al), etc. Among them, LiFePO4 has the advantages of high specific capacity (theoretical specific capacity is 170mAh / g), low price, non-toxicity, high safety, long life, etc. It is very suitable for application in the field of electric vehicles and has huge market opportunities.

[0003] With the development of power batteries, the performance requirements of the battery for the whole vehicle are getting higher and higher, especially the power performance of low SOC state of charge (State of Charge, SOC) and the power performance of low SOC at low temperature. For lithium iron phosphate lithium-ion batteries, the overall power performance of the battery can be significantly improved by means of positive electrode materials, electrolytes, etc., but this method will also lose performance such as energy density or life, and cannot solve the power problem of low SOC and low SOC at low temperature. Therefore, it is urgent to develop methods for improving power performance under low SOC and low SOC power conditions. Summary of the invention

[0004] In view of the above disadvantages of the prior art, the present invention provides a positive electrode material and a secondary battery to improve the low SOC power performance of the secondary battery.

[0005] To achieve the above-mentioned object and other related objects, the present invention provides a positive electrode material, which includes a first active material and a second active material, wherein the grain size d1 of the first active material is ≥80nm; and the grain size d2 of the second active material is <80nm.

[0006] In an example of the present invention, the first active material is a lithium iron phosphate material, and the second active material is a lithium iron phosphate material.

[0007] In an example of the present invention, the grain size d1 of the first active material satisfies: 80nm≤d1≤2000nm.

[0008] In an example of the present invention, the grain size d2 of the second active material satisfies: 0.1 nm≤d2≤70 nm.

[0009] In an example of the present invention, a discharge curve voltage of the second active material is lower than a discharge curve voltage of the first active material.

[0010] In an example of the present invention, the mass ratio of the first active substance to the second active substance is (70% to 97%): (3% to 30%).

[0011] In an example of the present invention, the mass ratio of the first active substance to the second active substance is (80% to 95%): (5% to 20%).

[0012] In an example of the present invention, the microscopic morphology of the second active material is nano-microspheres or nano-wires.

[0013] In one example of the present invention, the positive electrode material further includes a third active material, and the third active material includes at least one of a layered oxide positive electrode active material, a layered sulfide positive electrode active material, a spinel positive electrode active material, lithium manganese phosphate, and lithium manganese iron phosphate.

[0014] In one example of the present invention, the layered oxide positive electrode active material includes one or more of lithium cobalt oxide (LCO), lithium nickel cobalt manganese oxide (NCM), and lithium manganese-rich layered oxide (LLO); the layered sulfide positive electrode active material is selected from LiTiS2; the spinel positive electrode active material is selected from lithium manganese oxide (LMO).

[0015] The present invention also provides a secondary battery, which includes a positive electrode plate, a negative electrode plate, a separator and an electrolyte. The positive electrode plate includes a positive electrode collector and a positive electrode active material layer arranged on at least one side of the positive electrode collector, and the positive electrode active material layer includes the above-mentioned positive electrode material.

[0016] The positive electrode material of the present invention compounds an active material with a grain size greater than or equal to 80nm and an active material with a grain size less than 80nm. The active material with a large grain size can improve the energy density of the battery cell, and the discharge curve voltage of the active material with a small grain size is lower than the discharge curve voltage of the active material with a large grain size. When the battery cell is adjusted to a low SOC state and continues to discharge, the lithium insertion degree of the active material with large grains is close to the limit. At this time, the active material with small grains can continue to provide lithium insertion sites, thereby improving the low SOC power. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0018] Figure 1 The discharge curves of active materials with different grain sizes in the positive electrode material provided in one embodiment of the present invention, wherein the abscissa represents the content of lithium ions in the positive electrode material during the discharge process, and the ordinate represents the discharge voltage;

[0019] Figure 2 The present invention is a flow chart of a method for preparing a positive electrode material provided in one embodiment. DETAILED DESCRIPTION

[0020] The following is an explanation of the embodiments of the present invention by specific examples, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention. It should be noted that the features in the following embodiments and the embodiments can be combined with each other without conflict. It should also be understood that the terms used in the embodiments of the present invention are intended to describe specific embodiments, rather than to limit the scope of protection of the present invention. The test methods for which specific conditions are not specified in the following examples are usually carried out under conventional conditions or according to the conditions recommended by the manufacturers.

[0021] For simplicity, only some numerical ranges are explicitly disclosed herein, and each point or single value between the range endpoints is included in the range. Thus, each point or single value can be combined with any other point or single value as its own lower limit or upper limit or with other lower limits or upper limits to form an unspecified range.

[0022] First, several terms that may be involved in the embodiments of the present application are described:

[0023] A grain is a particle composed of unit cells arranged in the same orientation, where the orientation refers to the arrangement direction of the unit cell, and the unit cell is the smallest geometric unit that reflects the arrangement law of atoms in the crystal.

[0024] Grain size refers to the diameter or length of a grain in a crystal. The size of the grain will directly affect the performance of the material.

[0025] See also Figure 1The present invention provides a positive electrode material, which includes a first active material and a second active material. The grain size of the first active material is recorded as d1, and the grain size of the second active material is recorded as d2, then d1≥80nm; d2<80nm. The grain size of the first active material is relatively large, which can improve the energy density of the battery cell. The grain size of the second active material is relatively small. The discharge curve of the first active material is flatter than the discharge curve of the second active material. When discharged to a low SOC (lower than 5% SOC) state, the lithium insertion degree of the first active material is close to saturation, and it can no longer provide lithium insertion sites. The discharge curve of the second active material is in a low SOC state. The discharge curve voltage is lower than the discharge curve voltage of the first active material, and it can continue to provide lithium insertion sites. Therefore, compounding the first active material with a large grain size with the second active material with a small grain size can improve the low SOC power of the battery cell and enable the battery cell to continue to discharge in a low SOC state.

[0026] The first active material and the second active material are phosphate-based positive electrode active materials. As an example, the first active material and the second active material are both lithium iron phosphate (LiFePO4, referred to as LFP). Lithium iron phosphate can be directly purchased through general commercial channels, or prepared by referring to conventional preparation methods in the art, for example, by solid phase method: first, the phosphorus source, iron source, lithium source and carbon source are mixed and ground in proportion, spray dried to obtain a lithium iron phosphate precursor, and then the lithium iron phosphate precursor is sintered at high temperature to obtain lithium iron phosphate. Among them, the lithium source can be selected from lithium hydroxide or lithium carbonate; the iron source is selected from iron phosphate; the phosphorus source is selected from phosphoric acid, diammonium phosphate, etc., and the carbon source is selected from glucose, etc. Lithium iron phosphate can also be prepared by coprecipitation, hydrothermal or solvent thermal methods. The grain size of lithium iron phosphate can be adjusted by controlling the process conditions, for example, controlling the sintering temperature and sintering time to adjust its grain size.

[0027] Further, the grain size d1 of the first active material satisfies 80nm≤d1≤2000nm, and further, 80nm≤d1≤200nm, for example, d1 can be 80nm, 120nm, 200nm, etc. The grain size d2 of the second active material satisfies 0.1nm≤d2≤70nm, and further, 10nm≤d2≤50nm, for example, d2 can be 20nm, 30nm, 40nm or 50nm, etc.

[0028] In some embodiments, the mass ratio of the first active material and the second active material in the positive electrode material is (70% to 97%): (3% to 30%), the first active material is the main material, and its grain size is relatively large, which can make the battery cell have a better energy density, and a small amount of the second active material with small grains is added to the first active material to improve the power performance of the battery cell at low SOC. Further, the mass ratio of the first active material and the second active material is (80% to 95%): (5% to 20%), for example, the mass ratio of the first active material and the second active material can be 80%: 20%; or 90%: 10%; or 97%: 3%.

[0029] The grain size refers to the size of a single grain in a crystal, and this size can be the size of the grain in any direction. As an example, the grain size of the second active material is less than 80nm, which means that the size of the grain in any direction is less than 80nm, that is, the grain of the second active material can be a nanosphere, and the diameter of the nanosphere is less than 80nm; the grain of the second active material can be a nanowire, and the diameter of the nanowire is less than 80nm.

[0030] In some embodiments, the positive electrode material may further include a third active material, and the third active material may be selected according to the actual needs of the positive electrode material. As an example, the third active material includes at least one of a layered oxide positive electrode active material, a layered sulfide positive electrode active material, a spinel-type positive electrode active material, lithium manganese phosphate, and lithium manganese iron phosphate, that is, the third active material may be selected from any one of the above-listed types, or may be a combination of two or more of the above-listed types, such as a composition of a layered oxide positive electrode active material and a layered sulfide positive electrode active material mixed in any proportion, or a composition of a spinel-type positive electrode active material, lithium manganese phosphate, and lithium manganese iron phosphate mixed in any proportion, and the like. Among them, the layered oxide positive electrode active material includes one or more of LCO, NCM, and LLO, such as LCO; or NCM; or a composition of LCO and LLO mixed in any proportion, and the like; the layered sulfide positive electrode active material is selected from LiTiS2; and the spinel-type positive electrode active material is selected from LMO.

[0031] The preparation process of the positive electrode material of the present invention is as follows:

[0032] S1. Obtaining a first active substance and a second active substance;

[0033] S2. The first active material and the second active material are mixed uniformly in a certain ratio to obtain a positive electrode material.

[0034] The grain size d1 of the first active material in step S1 is ≥ 80 nm, and the grain size d2 of the second active material is < 80 nm. As an example, the first active material and the second active material are both lithium iron phosphate, and lithium iron phosphate with different grain sizes can be purchased through general commercial means, or prepared by conventional preparation methods in the art. For details, please refer to the relevant description above, which will not be repeated here.

[0035] Step S2: uniformly mix the first active substance and the second active substance in a mass ratio of (70% to 97%): (3% to 30%). The mixing method is not limited here, and can be any method that can uniformly mix the two, for example, mixing using a mixer.

[0036] On the other hand, the present invention provides a secondary battery, which includes a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte, wherein the positive electrode sheet includes the positive electrode material of the present invention. During the battery charging and discharging process, active ions are embedded and released back and forth between the positive electrode sheet and the negative electrode sheet; the separator separates the positive electrode sheet and the negative electrode sheet, and the electrolyte plays a role of conducting ions between the positive electrode sheet and the negative electrode sheet. Since the secondary battery of the present invention includes the positive electrode material of the present invention, the power performance of the battery at low SOC can be significantly improved.

[0037] Taking a lithium-ion secondary battery as an example, each component of the secondary battery is described in detail.

[0038] The positive electrode sheet includes a positive electrode current collector and a positive electrode active material layer disposed on at least one side of the positive electrode current collector, wherein the positive electrode current collector can be made of a material with good electrical conductivity and mechanical strength, such as aluminum foil. The positive electrode current collector has two surfaces opposite to each other in its own thickness direction, and the positive electrode active material layer can be disposed on any one or both of the two opposite surfaces of the positive electrode current collector. The positive electrode active material layer includes the above-mentioned positive electrode material, positive electrode conductive agent and positive electrode binder of the present invention, and the positive electrode binder can be selected from conventional binder types in the art, such as polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), etc. The positive electrode conductive agent is selected from one of carbon black, acetylene black, graphene, carbon nanotubes, carbon nanofibers, etc., or a combination of two or more mixed in any proportion.

[0039] The positive electrode sheet can be prepared according to methods known in the art. As an example, the positive electrode material, the positive electrode conductive agent and the positive electrode binder are dispersed in a solvent (such as N-methylpyrrolidone, referred to as NMP) to form a uniform positive electrode slurry: the positive electrode slurry is coated on the positive electrode current collector, and after drying, cold pressing and other processes, the positive electrode sheet is obtained. The ratio between the components in the positive electrode slurry can be set with reference to the conventional ratio, and is not limited here.

[0040] The negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer disposed on at least one side of the negative electrode current collector, wherein the negative electrode current collector is made of a material with good electrical conductivity and mechanical strength, such as copper foil. The negative electrode current collector has two surfaces opposite to each other in its own thickness direction, and the negative electrode active material layer can be disposed on any one of the two opposite surfaces of the negative electrode current collector, or on both surfaces of the negative electrode current collector. The negative electrode active material layer includes a negative electrode material, a negative electrode conductive agent, a negative electrode binder and a thickener, and the negative electrode material, the negative electrode conductive agent, the negative electrode binder and the thickener can all be materials known in the art that can be used in lithium-ion batteries, and those skilled in the art can select according to actual needs.

[0041] As an example, the negative electrode material is selected from any one of soft carbon, hard carbon, artificial graphite, natural graphite, silicon, silicon oxide compound, silicon carbon compound or a combination of at least two of them, that is, the negative electrode material can be any one of the materials listed above, or a combination of two or more materials mixed in any proportion, for example, a combination of soft carbon and hard carbon, a combination of artificial graphite and natural graphite, a combination of silicon, silicon oxide compound and artificial graphite, etc. The negative electrode conductive agent is selected from one of carbon black, acetylene black, graphene, carbon nanotubes, carbon nanofibers, etc. or a combination of two or more of them mixed in any proportion. The negative electrode binder is selected from any one of polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), styrene butadiene rubber (SBR) or a combination of several materials mixed in any proportion; the thickener is selected from carboxymethyl cellulose (CMC), which can be sodium carboxymethyl cellulose (CMC-Na) or lithium carboxymethyl cellulose (CMC-Li).

[0042] The negative electrode sheet can be prepared according to methods known in the art. For example, the negative electrode material, binder, thickener and conductive agent are dispersed in deionized water to form a uniform negative electrode slurry: the negative electrode slurry is coated on the negative electrode current collector, and after drying, cold pressing and other processes, the negative electrode sheet is obtained. Among them, the ratio between the components in the negative electrode slurry can be set according to the conventional ratio, and is not limited here.

[0043] The diaphragm is selected from conventional types in the art, for example, polyethylene with a thickness of 9 μm is used as a base film, and a nano-aluminum oxide coating with a thickness of 3 μm is coated on the base film to obtain a diaphragm.

[0044] The electrolyte is selected from a conventional combination type in the art, which includes an organic solvent, a lithium salt (selected according to the type of battery) and an additive, wherein the solvent can be selected from one of ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butylene carbonate (BC), etc., or a plurality of them mixed in any proportion. The lithium salt is selected from one of LiPF6 (lithium hexafluorophosphate), LiBF4 (lithium tetrafluoroborate), LiClO4 (lithium perchlorate), LiAsF6 (lithium hexafluoroarsenate), LiFSI (lithium bis(fluorosulfonyl)imide), LiTFSI (lithium bis(trifluoromethanesulfonyl)imide), LiTFS (lithium trifluoromethanesulfonate), LiDFOB (lithium difluorooxalate borate), LiBOB (lithium dioxalate borate), LiPO2F2 (lithium difluorophosphate), LiDFOP (lithium difluorobis(oxalate phosphate), LiTFOP (lithium tetrafluorooxalate phosphate) or a combination thereof in any proportion. The additive may include a film-forming additive and a functional additive that can improve battery performance. The specific types of additives are not described one by one here, and those skilled in the art may select according to actual needs.

[0045] The technical scheme of the present invention is described in detail below through several specific examples and comparative examples. Unless otherwise specified, the raw materials and reagents used in the following examples are all commercially available products, or can be prepared by conventional methods in the art, and the instruments used in the examples are all commercially available.

[0046] Example 1

[0047] The present embodiment provides a positive electrode material, which includes a first active substance and a second active substance, wherein the first active substance and the second active substance are lithium iron phosphate, wherein the grain size of the first active substance is 200 nm, the grain size of the second active substance is 40 nm, and the mass proportion of the first active substance in the positive electrode material is 80%, and the mass proportion of the second active substance is 20%.

[0048] The positive electrode material of this embodiment is assembled into a secondary battery, and the assembly process is as follows:

[0049] (1) Preparation of positive electrode sheet: The above positive electrode material is mixed with a binder of polyvinylidene fluoride (PVDF) and a conductive agent of conductive carbon black (Super P) in a weight ratio of 98:1:1, N-methylpyrrolidone (NMP) is added, and the mixture is stirred in a vacuum mixer until the system becomes uniform to obtain a positive electrode slurry; the positive electrode slurry is evenly coated on an aluminum foil current collector; the aluminum foil current collector coated with the positive electrode slurry is dried at room temperature and then transferred to an oven for drying, and then subjected to processes such as cold pressing and slitting to obtain a positive electrode sheet.

[0050] (2) Preparation of negative electrode sheets: The negative electrode material graphite is mixed with the conductive agent Super P, the thickener sodium carboxymethyl cellulose (CMC-Na), and the binder styrene-butadiene rubber (SBR) in a mass ratio of 96.6:0.4:1.2:1.8, and deionized water is added to obtain a negative electrode slurry under the action of a vacuum mixer; the negative electrode slurry is evenly coated on the negative electrode current collector copper foil; the copper foil current collector coated with the negative electrode slurry is dried at room temperature and then transferred to an oven for drying, and then subjected to processes such as cold pressing and slitting to obtain a positive electrode sheet.

[0051] (3) Preparation of electrolyte: In an argon atmosphere glove box with a water content of <10 ppm, battery-grade (referring to the purity level that meets the battery performance requirements) ethylene carbonate (EC), ethyl methyl carbonate (EMC), and diethyl carbonate (DEC) are mixed in a volume ratio of 1:1:1 to obtain an organic solvent. Then, fully dried lithium salt LiPF6 is dissolved in the mixed organic solvent to prepare an electrolyte with a concentration of 1 mol / L.

[0052] (4) Diaphragm: A PE porous membrane with a thickness of 11 μm is used as the diaphragm, wherein the air permeability is 180 s / 100 mL to 380 s / 100 mL and the porosity is 30% to 50%.

[0053] (5) Battery assembly: The prepared positive electrode sheet, separator, and negative electrode sheet are stacked in sequence, with the separator placed between the positive and negative electrode sheets to play a role of isolation. Then, they are wrapped with aluminum plastic film, dried, and injected with the above-prepared electrolyte. After packaging, standing, and formation, a soft-pack battery with a capacity of 1Ah (i.e., lithium-ion secondary battery) is finally obtained.

[0054] Example 2

[0055] The difference between this embodiment and embodiment 1 is that the mass proportion of the first active material in the positive electrode material is 90%, and the mass proportion of the second active material is 10%.

[0056] Example 3

[0057] The difference between this embodiment and embodiment 1 is that the mass proportion of the first active material in the positive electrode material is 95%, and the mass proportion of the second active material is 5%.

[0058] Example 4

[0059] The difference between this embodiment and embodiment 1 is that the mass proportion of the first active material in the positive electrode material is 95%, the mass proportion of the second active material is 5%, and the second active material is lithium iron phosphate nanowires with a diameter of 40 nm.

[0060] Example 5

[0061] The difference between this embodiment and embodiment 1 is that the grain size of the first active material is 80 nm, and the grain size of the second active material is 10 nm.

[0062] Example 6

[0063] The difference between this embodiment and embodiment 1 is that the grain size of the first active material is 120 nm, and the grain size of the second active material is 70 nm.

[0064] Comparative Example 1

[0065] The difference between Comparative Example 1 and Example 1 is that the positive electrode material only includes the first active material.

[0066] The secondary batteries assembled in Examples 1 to 6 and Comparative Example 1 were subjected to performance tests. The test process is as follows. The test results are shown in Table 1.

[0067] (1) Low SOC power test at room temperature: A pulse charge and discharge test was performed on a 5% SOC lithium iron phosphate battery at 25°C using an increasing current. A series of current and voltage curves were plotted for fitting to find the maximum discharge current I before the battery reaches the cut-off voltage V at 5% SOC. The maximum discharge power P of the battery at this SOC was obtained by multiplying the discharge cut-off voltage. The cut-off voltage for the charge and discharge test was 2.0V.

[0068] The power P=I*V is calculated according to the following formula, and the power of the battery of the comparative example (material before improvement) is recorded as P0. The power performance of each embodiment compared with the comparative example is α=P / P0*100%.

[0069] (2) Low SOC power test at low temperature: Pulse charge and discharge test was performed on 5% SOC lithium iron phosphate battery at -20℃ using increasing current. A series of current and voltage curves were plotted for fitting to find the maximum discharge current I before the battery reaches the cut-off voltage V at 5% SOC. Multiplying by the discharge cut-off voltage, the maximum discharge power P of the battery at this SOC was obtained. The cut-off voltage is 2.0V.

[0070] The power P=I*V is calculated according to the following formula, and the power of the battery of the comparative example (material before improvement) is recorded as P0. The power performance of each embodiment compared with the comparative example is α=P / P0*100%.

[0071] (3) Capacity retention rate test at low temperature: At 25°C, the lithium iron phosphate battery was charged to 3.65V at a constant current of 1C, and then charged to a current of less than 0.05C at a constant voltage of 3.65V. After standing for 10 minutes, it was discharged to 2.0V at a constant current of 1C. The discharge capacity of the lithium iron phosphate battery at this time was tested and recorded as the normal temperature discharge capacity. After the battery cell was fully charged under the above conditions, it was adjusted to a temperature box of -20°C. After reaching temperature equilibrium, it was discharged to 2.0V at a constant current and the discharge capacity of the battery at this time was tested and recorded as the low temperature discharge capacity. The low temperature capacity retention rate was calculated according to the following formula:

[0072] Capacity retention rate (%) = (low-temperature discharge capacity / normal-temperature discharge capacity) × 100%.

[0073] Table 1: Performance test results of batteries assembled from Examples 1 to 6 and Comparative Example 1

[0074]

[0075] By comparing Examples 1 to 3 with Comparative Example 1, it can be seen that compounding a certain proportion of small-grained second active material with the large-grained first active material can significantly improve the low SOC power performance and low-temperature capacity retention rate of the battery cell, and as the amount of small-grained active material increases, the performance improvement gradually decreases. When the mass ratio of large-grained active material to small-grained active material is 85:15, the performance reaches the best.

[0076] Comparing Example 3 with Example 4, the microscopic morphology of the small-grain active material will also have a certain impact on the improvement of its performance. The power performance of the nano-granular small-grain active material is more significantly improved at low SOC than that of the nano-wire small-grain active material.

[0077] By comparing Example 1, Example 5, Example 6 and Comparative Example 1, it can be seen that the grain size of the large-grain active substance and the small-grain active substance also affects the improvement of their performance. The greater the difference in grain size between the large-grain active substance and the small-grain active substance, the more obvious the improvement in their performance.

[0078] The present invention provides a positive electrode material and a secondary battery, which are compounded by large-grain active materials and small-grain active materials, using large-grain active materials to improve the energy density of the battery core, and using small-grain active materials to improve the low SOC power performance of the battery core. Therefore, the present invention effectively overcomes some practical problems in the prior art and has high utilization value and use significance.

[0079] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical concept disclosed by the present invention shall still be covered by the claims of the present invention.

Claims

1. A positive electrode material, characterized in that: include: A first active material, wherein the grain size d1 of the first active material is ≥80 nm; The second active material has a grain size d2 < 80 nm.

2. The positive electrode material according to claim 1, characterized in that The first active material is a lithium iron phosphate material, and the second active material is a lithium iron phosphate material.

3. The positive electrode material according to claim 1, characterized in that The grain size d1 of the first active material satisfies: 80nm≤d1≤2000nm.

4. The positive electrode material according to any one of claims 1 to 3, characterized in that: The grain size d2 of the second active material satisfies: 0.1 nm≤d2≤70 nm.

5. The positive electrode material according to claim 1, characterized in that A discharge curve voltage of the second active material is lower than a discharge curve voltage of the first active material.

6. The positive electrode material according to claim 1, characterized in that The mass ratio of the first active material to the second active material is (70% to 97%): (3% to 30%).

7. The positive electrode material according to claim 6, characterized in that The mass ratio of the first active substance to the second active substance is (80% to 95%): (5% to 20%).

8. The positive electrode material according to claim 1, characterized in that The microscopic morphology of the second active material is nano-microspheres or nano-wires.

9. The positive electrode material according to claim 1, characterized in that The positive electrode material further includes a third active material, and the third active material includes at least one of a layered oxide positive electrode active material, a layered sulfide positive electrode active material, a spinel positive electrode active material, lithium manganese phosphate, and lithium manganese iron phosphate.

10. A secondary battery, characterized in that: It comprises a positive electrode plate, a negative electrode plate, a separator and an electrolyte, wherein the positive electrode plate comprises a positive electrode collector and a positive electrode active material layer arranged on at least one side of the positive electrode collector, and the positive electrode active material layer comprises the positive electrode material as claimed in any one of claims 1 to 9.

Citation Information

Patent Citations

  • Method of preparing lithium iron phosphate having high conductivity and superior low temperature discharge property

    CN101407319A

  • Active material, electrode, secondary battery, battery pack, electric vehicle, electric energy storage system, electric power tool, and electronic unit

    CN102969500A

  • Method for preparing nanometer lithium iron phosphate for low temperature service

    CN103531793A

  • Method of judging lithium ion battery material performance based on grain size

    CN108427049A

  • Lithium iron phosphate cathode material, preparation method thereof and battery

    CN110127646A